2009
DOI: 10.1007/s00227-009-1333-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of seagrasses and algae of the Caulerpa family on hydrodynamics and particle-trapping rates

Abstract: The widespread decline of seagrass beds within the Mediterranean often results in the replacement of seagrasses by opportunistic green algae of the Caulerpa family. Because Caulerpa beds have a different height, stiffness and density compared to seagrasses, these changes in habitat type modify the interaction of the seafloor with hydrodynamics, influencing key processes such as sediment resuspension and particle trapping. Here, we compare the effects on hydrodynamics and particle trapping of Caulerpa taxifolia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
67
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 103 publications
(69 citation statements)
references
References 37 publications
1
67
0
1
Order By: Relevance
“…The SAR in seagrass meadows is mainly controlled by the canopy structure, which affects the trapping and retention of sediment particles (Gacia and Duarte, 2001;Peralta et al, 2008;Hendriks et al, 2010), the hydrodynamic energy, the availability of fine-grained suspended particles in the water column and the production of biogenic carbonates within the meadow (De Falco et al, 2000Mazarrasa et al, 2015). High plant biomass and density is associated with greater retention of particles (in particular, fine-grained sediments), lower hydrodynamic energy and higher production of biogenic carbonates within the meadow (De Falco et al, 2000), ultimately enhancing soil accumulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The SAR in seagrass meadows is mainly controlled by the canopy structure, which affects the trapping and retention of sediment particles (Gacia and Duarte, 2001;Peralta et al, 2008;Hendriks et al, 2010), the hydrodynamic energy, the availability of fine-grained suspended particles in the water column and the production of biogenic carbonates within the meadow (De Falco et al, 2000Mazarrasa et al, 2015). High plant biomass and density is associated with greater retention of particles (in particular, fine-grained sediments), lower hydrodynamic energy and higher production of biogenic carbonates within the meadow (De Falco et al, 2000), ultimately enhancing soil accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…The rates of soil accumulation, the sediment structure and the biochemical composition of the organic matter buried may strongly influence C org accumulation and preservation, and are highly variable among seagrass meadows (De Falco et al, 2000;Kennedy et al, 2010;Duarte et al, 2013). Soil accumulation may be a function of the seagrass canopy structure (De Falco et al, 2000;Gacia and Duarte, 2001;Peralta et al, 2008;Hendriks et al, 2010), the availability of suspended particles to settle outside of the water column and the production of biogenic carbonates within the meadow (De Falco et al, 2000;Mazarrasa et al, 2015). If the accumulated sediments are fine, then they are likely to enhance the preservation of C org since they tend to limit oxygen exchange and redox potentials, which reduce remineralization (e.g., Keil and Hedges, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Particle and phytoplankton trapping, carbon sedimentation rates, and sediment organic matter concentrations are higher in C. taxifolia beds than in adjacent bare sediments but similar to adjacent seagrass beds (Posidonia spp.) Holmer et al 2009;Hendriks et al 2010). Water column dissolved oxygen concentrations are lower, and sediment H 2 S and acid volatile sulfide (AVS) concentrations are higher in C. taxifolia beds than in adjacent bare sediments Holmer et al 2009).…”
mentioning
confidence: 99%
“…Reed et al (2009) demonstrated a similar correlation between reproductive structures and seed numbers in Phyllospadix torreyi. Seagrass canopies increase particle retention (Hendriks et al, 2010), so the presence of mature plants is likely to increase the retention of seeds as well as the sediment that may retain them even after the mature plants die back. These observations suggest that R. maritima populations may be relatively closed.…”
Section: Discussionmentioning
confidence: 99%